Effect of Application Rhizobakter and Fungi Arbuscular Mycorhiza (Fma) on Growth and Results of Potato (Solanum tuberosum L.) - Veriani, Weni; Warnita, Prof. Dr. Ir.; Dwipa, Dr. Ir. Indra; Irfan, Dr. Ir. Zul (International Journal of Environment, Agriculture and Biotechnology, 2019)
Indonesia national potato production is still relatively low compared with other countries. National potato production in 2017 range from 1,164,738 tonnes with an average per hectare production of western Sumatra 15.4 and 40 398 tonnes with an average of 19.37 tonnes per hectare (CBS, 2018). While the production of other countries such as: Australia 39.69 tonnes / ha, with 47.15 tonnes / ha, Japan 30.65 tonnes / ha and Laos 30.04 tonnes / ha. The low productivity of potato in Indonesia can be caused by several factors, such as the limited avaiNARility of nutrients, poor quality seeds, post-harvest handling of seed and farming systems that are less good. One important factor that greatly affects the growth and yield of potato crop is limited nutrients provided one of them is' phosphate.Phosphate is an essential nutrient that is needed for the plants in regulating physiological processes of plants. So to improve the growth and yield of potatoes should be given rhizobakteri and arbuscular mycorrhizal fungi (AMF). Rhizobakter type used in this research iswithout rhizobakteri, RZ1.L2.4, RZ1.L2.1, RZ2.L2.1 while the FMA dose is 5 g, 10 g and 15 g. The best treatment for the growth and yield of potato crop is rhizobakteri RZ2.L2.1 with a dose of 5 g FMA because it can increase net assimilation rate and leaf area index